Incorporation of localizing gradient-enhanced damage model into layered membrane elements for reinforced concrete structures subject to in-plane loading - Tong, Teng; Wang, Yangchun; Yuan, Siqi; Brigham, John C.; Liu, Zhao (Structures (Oxford), 2021)
•Unite localizing gradient-enhanced concrete model and Menegotto-Pinto steel model.•Propose eight-node quadrilateral layered membrane elements enhanced with DOFs.•Identify governing parameters and validate proposed RC element. Implementation of the localizing gradient-enhanced concrete model and the Menegotto-Pinto steel model into eight-node quadrilateral layered membrane elements for reinforcement concrete (RC) members subject to in-plane quasi-static loading is presented and evaluated. This RC element circumvents the pathological mesh-sensitivity of continuum damage models and the spurious damage growth of standard gradient damage models. Drilling DOFs are adopted, which improve the smoothness of strain distributions and aid in numerical convergence. The layered cross-section consists of fully bonded/smeared steel reinforcement layers and concrete layers. Different properties over the thickness can be easily assigned to each layer to account for heterogeneity. Several benchmark tests are simulated to demonstrate the versatility and effectiveness of the RC element. It is highlighted that all analyses are performed with the fully implicit incremental-iterative Newton-Raphson algorithm. Consequently, the RC element is suitable for modeling quasi-static behaviors of RC members, especially those coupled with other physical processes (creep, shrinkage, corrosion, etc.).